Maturity onset diabetes of the young due to HNF1A variants in Croatia - Pavić, T; Juszczak, A; Pape Medvidović, E; Burrows, C; Šekerija, M; Bennett, A; Ćuća Knežević, J; Gloyn, A; Lauc, G; McCarthy, M; Gornik, O; Owen, K (Croatian Society of Medical Biochemistry and Laboratory Medicine, 2018)
Introduction Maturity onset diabetes of the young due to HNF1A mutations (HNF1A-MODY) is the most frequent form of monogenic diabetes in adults. It is often misdiagnosed as type 1 or type 2 diabetes, but establishing genetic diagnosis is important, as treatment differs from the common types of diabetes. HNF1A-MODY has not been investigated in Croatia before due to limited access to genetic testing. In this study we aimed to describe the characteristics of young adults diagnosed with diabetes before the age of 45 years, who have rare HNF1A allele variants, and estimate the prevalence of HNF1A-MODY in Croatia. Materials and methods We recruited 477 C-peptide positive and beta cell antibody negative subjects through the Croatian Diabetes Registry. HNF1A was sequenced for all participants and systematic assessment of the variants found was performed. The prevalence of HNF1A-MODY was calculated in the study group and results extrapolated to estimate the proportion of diabetic individuals with HNF1A-MODY in Croatia and the population prevalence. Results Our study identified 13 individuals harbouring rare HNF1A allelic variants. After systematic assessment, 8 were assigned a diagnosis of HNF1A-MODY. Two individuals were able to discontinue insulin treatment following the diagnosis. We estimated that HNF1A-MODY in Croatia has a prevalence of 66 (95% CI 61 - 72) cases per million. Conclusions The estimated prevalence of HNF1A-MODY in Croatia is similar to that reported in other European countries. Finding cases lead to important treatment changes for patients. This strongly supports the introduction of diagnostic genetic testing for monogenic diabetes in Croatia.